Municipal Strategic Self-Assessment status and financial performance of water- boards - Matlala, Moloko (University of the Witswatersrand, Johannesburg, 2023)
This research is part of the MBA study, which was funded and supported by the national Department of Water and Sanitation as part of the employee bursary scheme. I am so thankful that the Department afforded me this opportunity to study MBA part-time. My supervisor at the Department of Water and Sanitation is gratefully acknowledged for approving all my study leave. I would like to thank my supervisor Dr Len Konar for the guidance and support he provided during this research journey. Without him, this research would not have been possible to be completed. My sincere thanks to my mentee, Dr MM Photolo for assisting me during the collection of data, document editing, and for all the discussions we had regarding my research. My work colleagues at the units: institutional oversight, and water services management were very helpful to provide this study with annual reports of water-boards and MuSSA reports for municipalities. I am grateful to Mr Sipho Mosai, CEO of Randwater, for those telephone calls that I had to make to confirm information in their annual reports. Many thanks to my family for the love, moral support, motivation, and financial help. Special thanks to my children for understanding and giving me the opportunity to study for the MBA degree
A research article submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Business Administration
Keywords: Municipal Strategic; Self-Assessment statu; UCTD; Financial performance of water- boards; SDG-8: Decent work and economic growth